THE IMPACT OF MEDIA ON THE FORMATION OF SOCIAL CONSCIOUSNESS IN OLDER PRESCHOOL CHILDREN (Conferencea, 2022)
In article influence of media environment on formation of social experience of children of preschool age is analyzed. Positive and negative sides of media education of preschool children are lit. The role of parents and teachers in the course of formation of social experience under the influence of media environment is characterized. Councils for improvement of positive impact of a media environment on formation of social experience of preschool children are offered.